Synthesis and characterization of an acrylate polymer containing chlorine-1,3-dioxalane groups in side chains - Ilter, Zulfiye; Alhanli, Ferhat; Dogan, Fatih; Kaya, Ismet (Springer, 2012)
Poly[2-(4-chlorophenyl)-1,3-dioxolan-4-yl]methyl acrylate, poly(CPhDMA), was synthesized with radical polymerization process using 2,2'-azobisisobutyronitrile as radical initiator in 1,4-dioxane at 60A degrees C. The structure of poly(CPhDMA) was confirmed by means of UV-Vis, FT-IR, H-1-NMR, and C-13-NMR spectral techniques. The molecular weight distribution values of the polymer were determined with gel permeation chromatography (GPC). The number-average molecular weight (M (n)), weight-average molecular weight (M (w)) and polydispersity index (PDI) values of poly(CPhDMA) were determined to be 10300, 21600 and 2.097, respectively. The thermal degradation kinetics of the polymer was investigated by using TG/DTG-DTA and DSC analyses at different heating rates in dynamic nitrogen atmosphere. The apparent activation energy values obtained by Flynn-Wall-Ozawa and Friedman methods were found to be 91.68 and 85.23 kJ mol(-1), respectively, for thermal decomposition of poly(CPhDMA). Also, the thermal degradation activation energy value of poly(CPhDMA) was calculated by using the Kissinger method based on the DTG, DTA and DSC data. Then the mechanism function of it was determined by master plots method. Finally, electrical and optical properties of poly(CPhDMA) were determined by four-point probe and UV-Vis techniques, respectively.
Keywords: Synthesis of acrylate polymer; Thermal degradation; Kinetic parameters